Negotiating the challenges in speaking English for Indonesian undergraduate students in an ESL university - Winnie, Winnie; Leong, Hugh John; Badiozaman, Ida Fatimawati; Yap, Alyssa (Universitas Syiah Kuala, 2023)
In Indonesia, English is not widely used for communication. Hence, Indonesian high school graduates who desire to study abroad may encounter difficulties communicating in English. One of the destination countries Indonesian students choose to study in is Malaysia. When studying in Malaysia, some may transition from EFL (English as a Foreign Language) to ESL (English as a Second Language) speakers as they are required to speak English more frequently, especially in academic contexts. Thus, this study was conducted to investigate the challenges of speaking English for Indonesian undergraduate students, the contributing factors to the challenges, and the strategies used by the students to navigate the challenges. A number of 15 Indonesian EFL undergraduate students still registered as active students in an ESL university in Malaysia participated in this study. Data was collected via semi-structured interviews, transcribed, and thematically analysed. The findings were presented thematically with narrative excerpts to support them. The results indicated some challenges faced when students adjusted themselves in their higher education institution, including their psychological reactions, speaking academic English, and online learning. Therefore, to help EFL students be more prepared to speak English for academic contexts in an ESL environment, stakeholders in the education sector in Indonesia should consider providing more actions to focus on improving the English-speaking skills of students.